C2H2 gas laser inside hollow-core photonic crystal fiber based on population inversion - Jones, Andrew M.; Nampoothiri, A. V. Vasudevan; Ratanavis, Amarin; Kadel, Rajesh; Wheeler, Natalie V.; Couny, Francois; Benabid, Fetah; Rudolph, Wolfgang; Washburn, Brian R.; Corwin, Kristan L. (Institute of Electrical and Electronics Engineers, 2010)
Lasing from population inversion is demonstrated from gas contained in a hollow-core kagome structured photonic crystal fiber. Laser pulses in the mid-IR (3.1-3.2 μm) were generated by optically pumping at λ ~ 1.5 μm.
Keywords: Molecular gas lasers; Lasers, fiber; Photonic crystal fibers